Integration of non-verbal audio in educational courseware / Prasanna Ramakrisnan ... [et al.] - Ramakrisnan, Prasanna; Mat Zain, Nurul Hidayah; Hasrol Jono, Mohd Nor Hajar; Za'ba, Nurmaisara; Abdul Aziz, Azlan (Penerbit UiTM (UiTM Press), 2008)
This research will identify situations where non-verbal audio is integrated in educational courseware. Previously there were no standards to integrate the non-verbal audio in educational courseware. Practically the integration of the audio usually depends on the designer of the courseware thus it can be declared as an ineffective way to use the non-verbal audio. This research is conducted to improve the proper usage of non-verbal audio and identify which part of the educational courseware it needs to be used. An informal analysis technique was designed to identify the proper cue to add the non-verbal sound in the educational ourseware. Interactions in courseware can be in the form of events, status or modes. Interaction is usually used to find information and this information will be delivered to user(s) in the form of feedback.